The Role of Bhejingan in The Selection of Village Chief - Romadhan, Ach Apriyanto (Government Studies of Muhammadiyah Malang University/AIPPTM, 2018)
This research was conducted with the aim to find out the role of bhejingan in the election of the village chief in Pamekasan. Based on data from Police Resort Pamekasan, utilization of bhejingan also in hardness, coloring election allegedly the head of a village in Pamekasan. In addition to votes may give rise to insecurity, involvement of bhejingan in the election of the village chief in value can reduce democratic values ... This study used a qualitative approach to the types of descriptive research. Source data obtained through interviews, participant observation and documentation. Based on the research results obtained information that role of bhejingan’s role in the selection of village chief political strategy performing various functions to help the village chief candidate's victory, among them: developing intercultural communication fellow bhejingan, charting the direction of the voice of the supporters, keeping the voice directions as well as mobilizing votes (money politic).